2013
DOI: 10.4045/tidsskr.11.1340
|View full text |Cite
|
Sign up to set email alerts
|

Fastlegetilhørighet og sykefravær – en registerbasert studie

Abstract: RESULTATER Fastlegenes alder, kjønn og listelengde var ikke assosiert med sykefravaer betalt av Nav. Sannsynlighet for sykefravaer > 16 dager ble redusert for både kvinner og menn når listen inneholdt mange høyt utdannede, høy andel eldre og få uførepensjonister. Menn på lister med høy andel menn og lister med høy andel yrkesaktive hadde også lavere odds for sykefravaer > 16 dager. For kvinner var sykefravaeret lavere ved åpne lister enn ved lukkede lister.FORTOLKNING I tillegg til velkjente individuelle fakto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
2
0
1
Order By: Relevance
“…The ‘dual role’ as advocate for the patient and gatekeeper for the social security system has been the focus of many—mostly qualitative—studies (25–28). However, two empirical studies from the UK (1,14) and two from Norway (29,30) found no significant variations in sickness certification between GPs, though low socioeconomic status of the practice population predicted more sickness certification, adjusted for individual variables (1,14,30). …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The ‘dual role’ as advocate for the patient and gatekeeper for the social security system has been the focus of many—mostly qualitative—studies (25–28). However, two empirical studies from the UK (1,14) and two from Norway (29,30) found no significant variations in sickness certification between GPs, though low socioeconomic status of the practice population predicted more sickness certification, adjusted for individual variables (1,14,30). …”
Section: Discussionmentioning
confidence: 98%
“…Contextual variables like location of practices and socio-economic status of practice populations have been used in some previous studies (1,30) and would have given a broader perspective. The study used data from 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Det at legen i liten grad attesterte sykmeldinger, påvirket altså ikke i saerlig grad fravaeret. I dette nummer av Tidsskriftet presenterer Lee Winde og medarbeidere en studie som viser at fastlegeeffektene forsvinner når man kontrollerer for listesammensetningen (4). Studien bygger på sykmeldingsdata fra Statistisk sentralbyrå koblet med Fastlegeregisteret.…”
unclassified